PWE-015 Can a negative fit test avoid the need for a routine surveillance colonoscopy?. (17th June 2017) - Digby, J; Cleary, S; Datt, P; Grey, L; Johnston, K; Goudie, D; Steele, B; Humphries, A; Strachan, J; Mowat, C
Abstract : Introduction: Faecal Immunochemical Tests for haemoglobin (FIT) detect haemoglobin in stool (FHb). FIT has been advocated as a good 'rule-out' test for significant bowel disease in the symptomatic population (1) . In this pilot study, we examined whether FIT may have a similar role in subjects enrolled in surveillance colonoscopy. Method: Between 1 st June 2014 and Sept 30 th 2016, 15 consecutive months of surveillance patients were approached at Ninewells Hospital, and 3 consecutive months were approached at St Marks Hospital. Subjects were invited to complete a FIT test prior to their colonoscopy. FHb was measured by Blood Sciences, Ninewells Hospital using an OC-Sensor iO analyser (Eiken Chemical Co., Tokyo, Japan) with an analytic range of <10 to>200 µg Hb/g of faeces. Colonoscopy results were recorded and the diagnostic accuracy of the FIT test was examined. Results: Of the 1103 patients approached, 643 returned a FIT kit. Four patients had known IBD and were excluded, leaving 639 (58%) in the study; age range 25–90 years (median 64 years, IQR 55–71) 54% were male. Indications for colonoscopy were: adenoma surveillance 312 (48.8%), genetic surveillance 152 (23.8%), other family history 84 (13.1%), cancer follow-up 72 (11.3%), other 19 (3.0%). Of the 639 patients, 46 were excluded from analysis of FIT test performance; 19 patients did not respond to or cancelled colonoscopy appointment, 8 did not attend colonoscopy, 3 patients were not fit to attend, 3 no valid FIT result, 1 cancelled by nurse, 1 had CT colonoscopy, 2 colonoscopy incomplete, 9 colonoscopies not complete by end of study. Of 593 patients who returned a FIT and completed colonoscopy only 7% had significant neoplasia (4 cancers (0.7%), 37 HRA (6.3%)) and 0.8% had IBD. 227/593 patients (38%) had undetectable FIT of whom 2.2% had significant neoplasia (one cancer (0.4%), 4 HRA (1.8%)) and 0.4% had IBD. 366/593 patients (62%) had detectable FIT of whom 9.9% had significant neoplasia (3 cancers (0.8%), 33 HRA (9.0%)) and 1.1% had IBD. Using a FIT cut off level of 'not detectable', gave a NPV of 99.6% for CRC and 97.8% for CRC+HRA. 36/41 cases of advanced neoplasia would have been detected. One CRC and 4 HRA would have been missed. Conclusion: The yield of significant neoplasia at surveillance colonoscopy was low. A negative FIT was recorded in over one third of subjects and could be used as a 'rule-out' test to avoid unnecessary surveillance colonoscopy, at the expense of missing a very small proportion of significant neoplasia. Reference: . Mowat C, J Digby, Strachan JA, et al . Faecal haemoglobin and faecal calprotectin as indicators of bowel disease in patients presenting to primary care with bowel symptoms. Gut2016 Sept;65(9):1463–9. Disclosure of Interest: None Declared